Model Literasi Berbasis Kearifan Lokal di Desa Hatawano Kabupaten Buru - Ivana Goa; Susiati Susiati; Hasanudin Tinggapy; Kurniati Tuasalamony; Taufik Taufik; La Ode Achmad Suherman (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
The aims of this study are (1) to explore and describe various local wisdoms of the Hatawano community; (2) describe a media literacy model based on local wisdom to be applied to the Hatawano community. The method used in this study is a qualitative descriptive method with an ethnographic approach. Data were obtained from primary data and secondary data with data sources coming from community leaders, village officials, written data from the library or literature. The method in this study is non-participatory observation with field survey techniques (field study), interviews (interviews), documentation studies, and literature studies. The data analysis phase includes data reduction, data presentation, data verification, and data analysis. The results of the study prove that 1) the local wisdom of the Hatawano community includes a) local values ​​in Hatawano Village contain local values ​​through mutual agreement and are carried out for the common interest. One of them, the masorat tradition, the use of the persona in the community; b) Local skills; c) Local knowledge; d) Local law. 2) a literacy model based on local wisdom to be applied to the Hatawano community, namely the media literacy model used by the Hatawano Village community is Protectionist. The local wisdom-based model includes 4 elements, namely the ability to access, analyze, evaluate and produce messages.